Co-valorization of crude glycerol and low-cost substrates via oleaginous yeasts to micro-biodiesel: Status and outlook. (July 2023) - Zhao, Man; Wang, Yanan; Zhou, Wenting; Zhou, Wei; Gong, Zhiwei
Abstract: Microbial lipid prepared by oleaginous yeasts from low-cost substrates for biodiesel production is promising to realize commercial success. Millions of tons of crude glycerol are generated every year due to the widespread availability of biodiesel. Recently, crude glycerol has been widely reintegrated for microbial lipogenesis on a laboratory scale. This review provides an overview of the status of crude glycerol-to-lipids routes by the oleaginous yeasts with a particular emphasis on the potential for glycerol channeling into lipid synthesis. The supplementation of auxiliary nutritional components is emphasized for realizing high lipid production from crude glycerol via oleaginous yeasts. Co-valorization of crude glycerol and low-cost substrates (nutrients) including protein-rich wastes, wastewater sludge, and lignocellulosic materials has gathered wide attention as novel strategy for lipid overproduction. Particularly, co-fermentation of glycerol and lignocellulosic sugars showed synergistic effect for lipogenesis. Highly-efficient pretreatment strategies to overcome the rigid structure of lignocelluloses and facilitate the enzymatic digestibility included crude glycerol-based organosolv processes. Therefore, a more integrated concept coupling crude glycerol-based pretreatment and glycerol/lignocellulosic hydrolysates co-utilization was highlighted, allowing a novel biodiesel industry integrating the traditional biodiesel plants and the cellulosic lipid-based microbial cell factories. The lipid profiles prepared from different crude glycerol-to-lipid routes showed high similarity to vegetable oils and indicated high-quality biodiesel properties. The upgrading of crude glycerol and low-cost substrates to micro-biodiesel offered both economic and environmental benefits. Highlights: Crude glycerol is suitable for realizing high lipogenesis of oleaginous yeasts. Co-valorization of crude glycerol and low-cost materials fostered high lipogenesis. Combination of crude glycerol with biomass hydrolysates reached synergistic effect. Crude glycerol was highly integrated into the lignocelluloses-to-biodiesel routes. Biodiesel from crude glycerol-based media showed high-quality fuel properties.